Psoriasis in Pediatrics - Andrey L. Bakulev; Ekaterina E. Talnikova (Вопросы современной педиатрии)
Psoriasis is one of the most debatable topics in modern dermatology among the wide range of other dermatological diseases in childhood. The article provides current data on the epidemiology of psoriasis, its clinical features in different age groups, its triggering factors, differential diagnostics, possible comorbid conditions, as well as the quality of life of patients and their relatives.